Design, synthesis, and activity evaluation of selective inhibitors of anti-apoptotic Bcl-2 proteins: The effects on the selectivity of the P1 pockets in the active sites. Issue 21 (1st November 2016) - Wang, Mingping; Tian, Wei; Wang, Chongqing; Lu, Shihai; Yang, Chao; Wang, Juan; Song, Yunlong; Zhou, Youjun; Zhu, Ju; Li, Zhiyu; Zheng, Canhui
Graphical abstract: Abstract: The anti-apoptotic Bcl-2 proteins are attractive targets for anti-cancer drug development, and the discovery of their selective inhibitors has become a research focus. In this Letter, obvious differences in the P1 pocket of the active site between Bcl-2, Bcl-xL, and Mcl-1 proteins were proposed by the structural comparison of these proteins. As a result, the groups in their inhibitors binding to the P1 pockets may have significant effect on the selectivity for these proteins. Based on this hypothesis, five types of derivatives of the lead compoundB-1 were designed, and several highly selective inhibitors of Bcl-xL (E-1 ) or Mcl-1 proteins (G ) were found. The selective inhibitors of Mcl-1 protein found in this Letter provide new structural types for the development of novel antitumor agents.